Latest Oligocene to middle Miocene low-latitude calcareous nannofossil biostratigraphy and paleoenvironmental interpretations of stratigraphic well 4, Sinú-San Jacinto onshore basin, northwest Colombia. (June 2023) - Mejía-Molina, Alejandra; Flores, José-Abel; Guerrero, Javier
Abstract: Calcareous nannofossils are one of the main fossil groups used in the petroleum industry to determine the relative age and correlation of lithofacies identified in gas and oil wells. A limited number of biostratigraphic zonation schemes based on nanoplankton and paleoceanographic reconstructions have been suggested to onshore Colombian Caribbean. Most of them are compiled in several publications for the northern Colombian units (Mejía-Molina et al., 2008, 2010). In this study, a medium to high-resolution biostratigraphy study was carried out on one of the best-known Neogene sedimentary successions in the Sinú-San Jacinto onshore Basin, where the Stratigraphic Well 4 (SW4) was drilled by Ecopetrol, the Colombian state-run oil company. The nannoplankton biostratigraphic zonation proposed here constitutes the first calcareous nanoplankton research to construct a biochronologic scheme for the Neogene of northern Colombia, which has direct applications for oil exploration, global energy matrix and the transition to clean energy in the onshore areas of the Sinú-San Jacinto domain. The section studied has a thickness of ∼269 m and comprises mainly a very thick succession of claystone and mudstone with occasional intercalations of silty sandstones corresponding to the El Carmen Formation. The studied interval is assigned to the nannofossils Zones NP25 (CP19) to NN4 (CN3) of Martini (1971) and Okada and Bukry (1980), spanning from the latest Oligocene (latest Chattian) to middle Miocene (early Langhian), approximately 24 Ma to 15 Ma. Intervals without fossil content were identified in the record and could constitute hiatuses, but the nannofloral events, which define the limits of the biozones, can be identified. Global and regional climatic changes which occurred in the Caribbean region at those times are reflected in important changes in the fossil assemblages and abundance pattern of nanoplankton. These could indicate variability in environmental conditions linked to temperature and increased nutrients within the nannofossil communities in this part of the San Jacinto folded belt (SJFB), northwest Colombia. Middle Miocene Climate Optimum (MMCO) episodes of "blooming" intervals of Sphenolithus were identified, accompanied with a drastic reduction in total nannofossil abundance and CaCO3 content. Since the Caribbean geology is framed in a very complex scenario, the data acquired and presented in this research has a potential application to improve the current stratigraphy in the area, targeted to hydrocarbon exploration and studies related to the global energy matrix and the transition to clean energy. It also strengthens the paleoceanographic reconstructions based on these organisms at low latitudes. Highlights: A nannoplankton-based biostratigraphic scheme is proposed for the Paleogene-Neogene of northern Colombia. Biostratigraphic scheme with direct application for petroleum exploration and the global energy matrix in onshore areas of the Sinú-San Jacinto domain. Integrated approach using paleoecological and geochemical proxy record. Nannofossils as proxy of environmental changes of the Middle Miocene Climate Optimum. Contribution to the knowledge of marine paleoceanographic reconstructions in low latitudes.